Development of information management platform to improve the effectiveness and efficiency of agents performance: a case study approach / Fadhil Maulana, Rangga Waskito Bawono and Yohannes Kurniawan - Maulana, Fadhil; Bawono, Rangga Waskito; Kurniawan, Yohannes (Universiti Teknologi MARA, 2020)
The purpose of this research is to develop the features in the information management platform (Sociomile) and how to make it easier for users to respond of tickets (complaints and feedback) from consumers. The data collection for this research used direct interviews with users and modeling used the several diagrams to visualize the features on the Sociomile platform. The results of this research are to add and develop features in the Sociomile platform such as Channel, Chatbot, Broadcast, and Export Key Performance Indicator and Reporting. This new platform will create users easier and efficient using the features on Sociomile platform and it will give the impact on the speed and information accuracy for providing responses to consumers